Application of Balloon AngioplaSty with the dIstal protection of Stent Retriever (BASIS) technique for acute intracranial artery atherosclerosis-related occlusion - Yi, Ting-yu; Wu, Yan-min; Lin, Ding-lai; Pan, Zhi-nan; Zheng, Xiu-fen; Gan, Ji; Wu, Mei-hua; Lin, Xiao-hui; Chen, Rong-cheng; Zeng, Li-san; Chen, Wen-huo (Frontiers in Neurology, 2022)
Background Endovascular therapy (EVT) is complex in the context of intracranial atherosclerosis (ICAS)-related large vessel occlusion (LVO) and with poor prognosis due to high occlusion rates and long procedure time, and the optimal EVT technique is unclear. The BASIS technique is a novel thrombectomy technique that allows emergent balloon angioplasty to be performed via the wire of the retrieval stent. Our study presents our initial experience with the BASIS technique in ICAS-related LVO and assesses its feasibility. Method In patients with ICAS-related LVO treated with BASIS, clinical and angiographic data were retrospectively analyzed. Angiographic data included first-pass reperfusion (PFR), the rate of residual stenosis, distal emboli and re-occlusion post procedure. The Extended Thrombolysis in Cerebral Infarction (eTICI) scale was used to assess reperfusion extent, and an eTICI score ≥2b was defined as successful perfusion. Clinical outcome was evaluated at 3 months (modified Rankin score [mRS]), and an mRS ≤2 was defined as a good clinical outcome. Results A total of seven patients with ICAS-related LVO were included, and the median age of the patients was 76 years. All patients achieved eTICI 3 reperfusion and FPR. The residual stenosis rate ranged from 5%–10%. None of the patients had re-occlusion post-procedure. The median puncture-to-reperfusion time was 51 minutes. None of the patients had symptomatic cerebral hemorrhage, re-occlusion ,distal embolism , dissection. Good clinical outcomes were observed in 4 patients (4/7, 57.1%), and one patient (1/7, 14.3%) died. Conclusion The BASIS technique is feasible and safe for treating acute ICAS-related LVO.